ASSESMEN PEMBELAJARAN BOLA BASKET DI MASA PANDEMI COVID-19 - Adrianus Eldi Chrisantus Boby; Mimi Haetami; Muhammad Fachrurrozi Bafadal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem in this study is how the teacher assesses basketball learning during the pandemic, the teacher cannot conduct direct assessments in the field, the prohibition of face-to-face learning makes it difficult for teachers to make assessments in basketball learning, the purpose of this research is to find out the assessment. learning during the pandemic in junior high schools in Pontianak Selatan District, West Kalimantan, from several research methods the survey method was used in this study which used Google form media which contained questionnaires to junior high school teachers in South Pontianak District, in this study it was obtained The results through google form are developed through technology with a sample of sports teachers who live 16 in the city of Pontianak teaching publicly. The assessment level of learning basketball in Pontianak's first high school reaches a score of 75% consisting of several indicators of the items that are tested on average choosing yes ber a total of 24 items and not 8 items so that the voters did not amount to 25%. From the existing conclusions, the right suggestion is the need to always improve experience in the learning assessment process Basketball so that teacher knowledge is able to answer the where abouts of students.Keywords: basketball learning assessment